O sentido de corporeidade e a atuação profissional do professor de educação física do ensino médio público - Bonfim, Tânia Regina [UNESP] (2003)
Comparing studies that have been focusing attention on representations that physical education teachers have about their students body to ones that have identified a kind of students unhappiness to pedagogical/body practice of their teachers, the corporeidade question seems to show up as special to school physical education praxis. Because, to be a body is to be in a sensible world in an intelligent way through a learning dialogue, in a sense of living attitudes and finding bodies richer in vital and emotional sense. It is to know how to look at expressions and desires of the body and the body beside. Thus, it was purpose to investigate the process of construction of body sense of physical education teacher of public high school in relation to his profession. Participated of this study, five teachers, anybody's guess selected, from Rio Claro/SP City, being three women and two men, aged between 27 to 53 years old. All of them were licensed and they had studied on São Paulo State on 70's and 90's. As a methodological proceeding, to interpret the semi-structured interview done with them it was opted for the speech analyses. Subsidizing the interpretation of interviews, six classes were observed, in a participate way and not, of each teacher. In a general way, the speech analyses give us a direction to an amplified view of the world, assuming its incompleteness; trying to interpret the meaning, comprehend the discursive process of subject historically constituted. After analyses of results, it was possible to infer that the way as teachers interviewed understand and translate the body vision and consequently the corporeidade, has an influence in the way they teach their physical education classes in outlining of contends and purposes and in their posture to their students; constituting a process marked by the kinds of body experience that they have had in their personal and professional trajectory of life